2021
DOI: 10.1097/md.0000000000026962
|View full text |Cite
|
Sign up to set email alerts
|

Nalbuphine and dexmedetomidine as adjuvants to ropivacaine in ultrasound-guided erector spinae plane block for video-assisted thoracoscopic lobectomy surgery

Abstract: Background:Adjuvants to local anesthetics, such as nalbuphine and dexmedetomidine, can be used to improve the quality and duration of peripheral nerve block effects. Dexmedetomidine has been successfully used as an adjuvant of erector spinae plane block (ESPB) with ropivacaine in video-assisted thoracoscopic lobectomy surgeries (VATLS). This study aimed to compare the effects of nalbuphine and dexmedetomidine used as adjuvants to ropivacaine for ESPB in VATLS.Methods:A total of 102 patients undergoing VATLS wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…However, the time of using ropivacaine alone for a nerve block is short and the postoperative analgesic effect is limited. Dexmedetomidine combined with ropivacaine can enhance peripheral nerve block and prolong sensory block time ( 45 , 46 ). Our present study showed that ropivacaine plus dexmedetomidine (μg/kg−1) had better analgesic efficacy than ropivacaine alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the time of using ropivacaine alone for a nerve block is short and the postoperative analgesic effect is limited. Dexmedetomidine combined with ropivacaine can enhance peripheral nerve block and prolong sensory block time ( 45 , 46 ). Our present study showed that ropivacaine plus dexmedetomidine (μg/kg−1) had better analgesic efficacy than ropivacaine alone.…”
Section: Discussionmentioning
confidence: 99%
“…Rao et al. found that nalbuphine or dexmedetomidine as an adjuvant to ropivacaine in ultrasound guided erector spine plane block provided comparable pain control and prolonged sensory block duration in video-assisted thoracoscopic lobectomy surgery [ 32 ]. Consistent with previous studies, we found that the addition of nalbuphine prolonged the duration of analgesia and increased the sensory block area compared with ropivacaine alone.…”
Section: Discussionmentioning
confidence: 99%
“…When data were not presented in the original literature, we contacted the author to obtain the required information. Last resort, when means and SDs values were not available (the time rst to request rescue analgesia [19][20][21][22], number of PCIA presses [19,21,22]), these values were imputed using the calculation methods of two statistical experts McGrath [14] and Cai [15]. Data from trial [22] with two intervention groups receiving different doses of DEX were combined into a single group as per the Cochrane Handbook [16].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 8 RCTs were included in the study [19][20][21][22][23][24][25][26]. Fig 1 represents the preferred reporting items for systematic reviews and meta-analysis (PRISMA) ow diagram, and summarizes the reasons for exclusion of records [13].…”
Section: Study Selectionmentioning
confidence: 99%